2015
DOI: 10.1155/2015/712359
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodispersed Gold Nanoparticles with Exceptional Colloidal Stability with Grafted Polyethylene Glycol‐g‐polyvinyl Alcohol

Abstract: Herein, we report the synthesis of spherical gold nanoparticles with tunable core size (23–79 nm) in the presence of polyethylene glycol-g-polyvinyl alcohol (PEG-g-PVA) grafted copolymer as a reducing, capping, and stabilizing agent in a one-step protocol. The resulted PEG-g-PVA-capped gold nanoparticles are monodispersed with an exceptional colloidal stability against salt addition, repeated centrifugation, and extensive dialysis. The effect of various synthesis parameters and the kinetic/mechanism of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…www.wjpr.net The level of HAuCl 4 was found to decrease linearly over time period due to the reduction through green tea polyphenols as reported in Parkin et al [31][32] This phenomenon showed decrease in particle size of the PM-AuNPs. Hence the reaction time had a negative impact on the particle size, whereas there was no change in the % loading efficiency over the range of reaction time.…”
Section: Effect Of Gold Salt Concentration On Particle Size and Loadimentioning
confidence: 56%
“…www.wjpr.net The level of HAuCl 4 was found to decrease linearly over time period due to the reduction through green tea polyphenols as reported in Parkin et al [31][32] This phenomenon showed decrease in particle size of the PM-AuNPs. Hence the reaction time had a negative impact on the particle size, whereas there was no change in the % loading efficiency over the range of reaction time.…”
Section: Effect Of Gold Salt Concentration On Particle Size and Loadimentioning
confidence: 56%
“…The infrared (IR) band at 1096 cm À1 , 2927 cm À1 , 1704 cm À1 and 1461 cm À1 are characteristic vibration bands of kollicoat; and can be assigned to the vibration of the C-OH, C-H, C¼O and C-O bonds. 25 The bands at 3611 cm À1 , 3743 cm 1 and 3854 cm À1 can be assigned to -OH group. These IR bands con¯rmed the capping of kollicoat on the surface of Ag NPs.…”
Section: Characterization Of Synthesized Ag Npsmentioning
confidence: 99%
“…Alkilany et al have synthesized spherical gold nanoparticles using kollicoat as a stabilizing agent. 25 Manufacturing several analgesic and antipyretic drugs needs 4-aminophenol (4-AP) as a potent intermediate. It is also used exceptionally as a photographic developer, corrosion inhibitor, anti corrosion-lubricant and hair-dyeing agent.…”
Section: Introductionmentioning
confidence: 99%
“…However, polymers are broadly used in the green synthesis of AuNPs. Polymers employed as AuNPs stabilizers consider homopolymers such as poly(N-vinyl-2-pyrrolidone) PVP and poly(acrylic acid) PAA, block copolymers such as poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) PEO-PPO-PEO, and polyethylene glycol-g-polyvinyl alcohol PEG-g-PVA, among others [3,[33][34][35][36][37]. Stabilization of metal surfaces using polymers, offers the possibility of tuning the optical properties, functionality, and surface reactivity of metal nanoparticles [31].…”
Section: The Behavior Of Polymers In Gold Nanoparticle Synthesismentioning
confidence: 99%